Premarital sex and associated factors among unmarried students of a private college in Addis Ababa, Ethiopia - Birri, Dagim Jirata; Takele, Mihiretu Kumie (Ethiopian Journal of Reproductive Health, 2024)
Premarital sex may result in sexually transmitted infections (STIs) and unwanted pregnancy. Published reports on the prevalence premarital sex among private college students in Ethiopia are limited. This study aimed to assess the prevalence of premarital sex and associated factors among unmarried students of a private college in Addis Ababa, Ethiopia. A cross-sectional study was conducted and a structured questionnaire was used to collect data from 390 unmarried students of the college selected by stratified random sampling. Associations between variables were determined using logistic regression at P-value less than 0.05. The prevalence of premarital sex was 23.3%, and 20% started sex before 18. About 68% did not use condom at the first sex. Nearly 15.5% had multiple sexual partners. About 14.5% said oral contraceptive pills prevent STIs. Nearly 59 % did not have a practice of requesting a new sexual partner for STIs status. Regression analysis showed that religion, program of study, having a boyfriend or girlfriend, misconception that oral contraceptive pills protect from STIs and taking alcohol were significantly associated with having premarital sex. The prevalence of premarital was high among participants. Effective intervention strategies are needed to reduce the prevalence of premarital sex.